Reconstruction of limnology and microbialite formation conditions from carbonate clumped isotope thermometry. Issue 1 (January 2015) - Petryshyn, V. A.; Lim, D.; Laval, B. L.; Brady, A.; Slater, G.; Tripati, A. K.
Abstract Quantitative tools for deciphering the environment of microbialite formation are relatively limited. For example, the oxygen isotope carbonate‐water geothermometer requires assumptions about the isotopic composition of the water of formation. We explored the utility of using 'clumped' isotope thermometry as a tool to study the temperatures of microbialite formation. We studied microbialites recovered from water depths of 10–55 m in Pavilion Lake, and 10–25 m in Kelly Lake, spanning the thermocline in both lakes. We determined the temperature of carbonate growth and the 18O/16O ratio of the waters that microbialites grew in. Results were then compared to current limnological data from the lakes to reconstruct the history of microbialite formation. Modern microbialites collected at shallow depths (11.7 m) in both lakes yield clumped isotope‐based temperatures of formation that are within error of summer water temperatures, suggesting that clumped isotope analyses may be used to reconstruct past climates and to probe the environments in which microbialites formed. The deepest microbialites (21.7–55 m) were recovered from below the present‐day thermoclines in both lakes and yield radioisotope ages indicating they primarily formed earlier in the Holocene. During this time, pollen data and our reconstructed water 18O/16O ratios indicate a period of aridity, with lower lake levels. At present, there is a close association between both photosynthetic and heterotrophic communities, and carbonate precipitation/microbialite formation, with biosignatures of photosynthetic influences on carbonate detected in microbialites from the photic zone and above the thermocline (i.e., depths of generally <20 m). Given the deeper microbialites are receiving <1% of photosynthetically active radiation (PAR), it is likely these microbialites primarily formed when lower lake levels resulted in microbialites being located higher in the photic zone, in warm surface waters.